2015
DOI: 10.4330/wjc.v7.i6.315
|View full text |Cite
|
Sign up to set email alerts
|

Nomenclature, categorization and usage of formulae to adjust QT interval for heart rate

Abstract: Assessment of the QT interval on a standard 12 lead electrocardiogram is of value in the recognition of a number of conditions. A critical part of its use is the adjustment for the effect of heart rate on QT interval. A systematic search was conducted to identify studies that proposed formulae to standardize the QT interval by heart rate. A nomenclature was developed for current and subsequent equations based on whether they are corrective (QTc) or predictive (QTp). QTc formulae attempt to separate the depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…In the meta‐analysis of eight thalassaemia major studies (Table SIV), the random effects estimate of the raw mean difference of QTcB interval was 19·5 ms (95%CI = 8·6–30·3; P < 0·001) (Fig ) with heterogeneity Q‐value of 50·6 (degrees of freedom = 7, P < 0·001) and I 2 of 85. QT intervals were corrected for heart rate by Bazett's formula(Rabkin & Cheng, ) in seven out of eight studies; Oztarhan et al () did not mention which formula was used for correction. Subgroup analyses made by excluding one study at a time showed robustness of the random effects estimate (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meta‐analysis of eight thalassaemia major studies (Table SIV), the random effects estimate of the raw mean difference of QTcB interval was 19·5 ms (95%CI = 8·6–30·3; P < 0·001) (Fig ) with heterogeneity Q‐value of 50·6 (degrees of freedom = 7, P < 0·001) and I 2 of 85. QT intervals were corrected for heart rate by Bazett's formula(Rabkin & Cheng, ) in seven out of eight studies; Oztarhan et al () did not mention which formula was used for correction. Subgroup analyses made by excluding one study at a time showed robustness of the random effects estimate (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Since the QT interval is highly heart rate dependent, the corrected QT (QTc) interval was determined by heart rate using Fridericia's formula (QTc=QT/(60/normalheart4ptnormalrate)1/3) (Fridericia, ). Bazett's formula for heart rate correction of QT interval (QTcB=QT/normalRR) (Rabkin & Cheng, ) was used only in comparison with the meta‐analysis, when the variable will be referred to as QTcB.…”
Section: Methodsmentioning
confidence: 99%
“…Eligible interventions included atypical antipsychotics when compared with placebo or other antipsychotic medications. Eligible outcomes included change in QT Interval, clinically important prolongation of QT corrected to RR interval ≥450 msec in men ≥480 msec in women, and QTc ≥500 msec associated with increased risk of life-threatening torsades de pointes ventricular tachycardia (9).…”
Section: Methodsmentioning
confidence: 99%
“…A key issue in the utilization of the QT interval, is the need to appropriately adjust or correct for the impact of heart rate on the QT interval. Many formulae have been proposed to correct for the impact of heart rate on the QT interval so that the underlying QT interval can be assessed (for a review see [6]). The approach of Bazett, that the impact of heart rate can be corrected by dividing the QT interval by the square root of heart rate [7] and the approach of Fridericia that the QT interval needs to be divided by the cubed root of the heart rate (RR interval) [8], are still in use today.…”
mentioning
confidence: 99%
“…Mathematical equation -linear, exponential, cubic etc. have been applied to ECGs from patients and large populations in an attempt to adjust for the effect of heart rate on the QT interval [6]. Testing for the validity of approaches to adjust or correct for the impact of heart rate on the QT interval has been conducted within or between individuals and mainly in humans.…”
mentioning
confidence: 99%